Analysis of vegetable oils, seeds and beans by TGA and NMR spectroscopy - Retief, Liezel (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD (Chemistry and Polymer Science))--University of Stellenbosch, 2011.